Advocating Positive Traditional Culture to Eradicate Harmful Aspects of Traditional Culture for Gender Equality in Africa - Norah Hashim Msuya (Obiter, 2020)
The struggle for equality for all and the abolition of discriminatory, harmful cultural practices affecting women has been occurring in the world for some time now. Most African countries outlaw harmful, discriminatory traditional practices, although they persist, causing the violation of domestic and international human rights laws. Outside efforts to eliminate these practices are often met with suspicion or hostility from communities, because Africans generally believe that these are their valuable, traditional practices. The aim of this article is to discuss alleviating harmful traditional practices suppressing gender equality in Africa by practically supplementing the law. The study examines African culture versus gender equality historically to pinpoint colonialism’s influence in current gender equality. Colonial administration influenced lives politically, economically and socially, including culture and traditions. Efforts to eradicate harmful traditional practices are most effective when originating from within the culture, as focussing on international human rights is often perceived as culturally imperialistic in African countries.